Evaluation of the relationship between the Desire to Avoid Pregnancy Scale and contraceptive use among women living with HIV in western Kenya - Briend Donanty Kilone; Surya Sruthi Bhamidipalli; Caroline Kerich; Sammy Changwony; John Humphrey; Mercy Maina; Julie Thorne; Shukri A. Hassan; Mehar Maju; Kara Wools-Kaloustian; Beatrice Jakait; Rena C. Patel; et al. (Frontiers in Global Women's Health, 2026)
Background Unintended pregnancies place women living with HIV (WLHIV) at risk for maternal and neonatal adverse outcomes. Counseling around pregnancy preferences is important but complex, and there is insufficient evidence around best practices to assess and respond to reproductive health needs. Objective This study aimed to compare responses to the Desire to Avoid Pregnancy (DAP) scale to assess pregnancy preferences, with the dichotomous traditional question “Are you trying to become pregnant within the next one year?” and how these relate to current contraceptive use. Methods The study analyzed cross-sectional telephone interview data from the parent cohort study Chaguo Langu among WLHIV in western Kenya enrolled in HIV care in 2017–2020. Women underwent interviews about reproductive health and HIV care, including the DAP scale, the traditional question, and current contraceptive use. Multivariate logistic regression models were used to assess associations between DAP score, response to the traditional question, and contraceptive use, adjusting for age, marital status, and HIV treatment regimen. Results Among 1226 participants, the median DAP score was 2.94 [IQR: 1.93–3.14] and was higher among those reporting not trying to become pregnant compared to those who were trying (3.0 vs. 0.9, p < 0.01), though the distribution of scores overlapped. In multivariable logistic regression, participants with a higher DAP score were more likely to use a contraceptive method. Conclusions Among WLHIV, the DAP score captured a range of pregnancy preferences that correlated with the responses to the traditional dichotomous question and, less so, to contraceptive use. Further adaptations and testing would be needed to conclude whether DAP would be a better tool for assessment of nuances in pregnancy desires among WLHIV, including in Kenya, than the traditional dichotomous question.